A Study to Explore the Relationship between Dental Caries and Weight of the Slum Living Children in Dhaka - Riftana Mahjabeen; Dilruba Sharmin; Nabila Anwar; Syeda Rubaiya Nawshin; Sejuty Haque; Mahfujul Haq Khan (Update Dental College, 2016)
Background and Objectives: Dental caries or decay is the most significant dental disease of childhood in Bangladesh. It is also reported to affect the anthropometric outcomes of children. So the objective was to assess the relationship between dental decay and weight of the children living in various slum areas of Dhaka, Bangladesh. Methods: A cross-sectional study was conducted among the children in a slum area of Mirpur, Dhaka. The children were selected by using simple random sampling technique. A total of 310 children were interviewed and examined on the basis of the questions regarding their age, gender, height, weight, nutrition, socio-economic status and clinical conditions. Results: The study showed an inverse relationship between dental decay and weight among the children. Among 310 children about 40.64% were suffering from dental caries and 95.5% children were underweight. Children with at least one decayed tooth were significantly more likely to be underweight with odds ratios 0.614, 0.763 for the age group of below 6 years and above 12 years. Conclusion: The study depicted an inverse relationship between dental decay and weight among the children of slum dwellers in Dhaka and emphasized on the necessity of implementing proper dental health care policies and programs among those socio-economically deprived people. Update Dent. Coll. j: 2016; 6 (1): 21-29